A Habsburg Birodalom térképei a Bánságról : XVIII-XX. sz. - Suba, János (Közép-Európai Közlemények, 2010)
The 1st and 2nd military surveys of the Habsburg Empire were done by the countries and territories. The surveying of the Temes Banate was ordered by Empress Maria Theresa in 1769. This was a scale 1:7200 economic survey in order to exhibit the tenements, landed properties and to gain information on the land use. This preliminary survey served as a basis for the scale 1:28 800 segments of the 1st military survey of the empire in 1772. The mapping of the 2nd military survey (1865-1866) has already been connected to the mapmaking of the different countries of the empire, similarly to that of the 3rd military survey between 1872 and 1884. The exhibition contains some deduced maps besides the sheets of the surveys.